Analysis of Corticosterone and Testosterone Synthesis in Rat Salivary Gland Homogenates - Ieko, Takahiro; Sasaki, Hirokuni; Maeda, Naoyuki; Fujiki, Jumpei; Iwano, Hidetomo; Yokota, Hiroshi (Frontiers in Endocrinology, 2019)
Extra-adrenal steroid hormone production has been reported in several tissues, the biological role of which is interesting in terms of hormonal regulation of metabolism, growth, and behavior. In this report, we describe for the first time steroidogenesis in rat salivary glands. Enzyme activities associated with corticosterone and testosterone production were detected in rat salivary glands by LC-MS analysis. In tissue homogenates of rat salivary glands, progesterone was produced enzymatically in vitro from pregnenolone in the presence of NADPH and NADH. Deoxycorticosterone was produced from progesterone, corticosterone from deoxycorticosterone, and testosterone from androstenedione (but not pregnenolone from cholesterol) via enzymatic reactions using the same tissue homogenates. Immunoblotting analysis indicated the expression of 11β-hydroxylase (cytochrome P450 11β1; CYP11β1), which mediated the production of corticosterone from deoxycorticosterone. However, CYP family 11 subfamily A member 1 (CYP11A1)-mediated production of pregnenolone from cholesterol was not detected in the salivary glands by immunoblotting using a specific antibody. These results indicate that corticosterone and testosterone are produced from pregnenolone in rat salivary glands. The initial substrate in salivary steroidogenesis and the roles of salivary corticosterone and testosterone are discussed.